156k views
1 vote
I'm stuck on this question, I have to solve for "e"

I'm stuck on this question, I have to solve for "e"-example-1
User Viker
by
4.9k points

1 Answer

4 votes

Given the following equation shown in the picture:


(E)/(e)=(R+r)/(r)

You can solve for the variable "e" by following the steps shown below:

Step 1. You must apply the Multiplication property of equality by multiplying both sides of the equation by "e". As you can see below:


\begin{gathered} (e)((E)/(e))=(e)((R+r)/(r)) \\ \\ E=(e(R+r))/(r) \end{gathered}

Step 2. Now you must apply the Multiplication property of equality again by multiplying both sides of the equation by "r":


\begin{gathered} (r)(E)=(r)((e(R+r))/(r)) \\ \\ Er=(1)e(R+r) \\ Er=e(R+r) \end{gathered}

Step 3. Finally, apply the Division property of equality by dividing both sides of the equation by:


(R+r)

Then, you get:


\begin{gathered} (Er)/((R+r))=(e(R+r))/((R+r)) \\ \\ (Er)/(R+r)=e \end{gathered}

Therefore, the answer is:


e=(Er)/(R+r)

User Altaf Sami
by
5.0k points